Answer:
The given statement is False.
Step-by-step explanation:
Let us suppose a triangle ABC.
The law of cosine is given by
![c^2=a^2+b^2-2ab\cos C](https://tex.z-dn.net/?f=c%5E2%3Da%5E2%2Bb%5E2-2ab%5Ccos%20C)
And the Pythagorean theorem is given by
![c^2=a^2+b^2](https://tex.z-dn.net/?f=c%5E2%3Da%5E2%2Bb%5E2)
Now, in order to the law of cosine to be in the form of Pythagorean theorem, we must have 2abcos C =0.
a and b can't be zero since it represent the sides of the triangle. Hence, we have
cos C= 0
thus, the value of C is 90 degrees. Hence, the triangle must be a right angle triangle.
Thus, the triangle shouldn't be acute triangle.
Therefore, the given statement is false/